Mini Mobile Filtration with Activated Carbon Adsorbent and Powder of Bidara Leaf (Ziziphus Mauritiana) Leaf as Room Air Purifier - Nurul Amaliyah; Taufik Anwar; Slamet Wardoyo (Poltekkes Kemenkes Palu, 2023)
Forest fires have been a major threat for decades. Forest fire smoke can trigger high levels of highly toxic carbon-containing particles that are the source of carbon monoxide (CO), nitrogen monoxide (NOx), sulfur dioxide (SO2), and PM2.5. Exposure to COx, especially CO and SOx, can be detrimental to human health. To reduce exposure to toxins in smoke, researchers want to make a mini-mobile filtration system of activated carbon and bidara leaf powder. This study is quasi-experimental, where both groups were measured to determine the initial condition. The experimental group was treated, and the comparison group was not. After the completion of treatment, both groups were measured as a posttest to determine the final condition. The result is there was a decrease in COx, SOx, and particulate matter values by 57%, 51%, and 37%. The conclusion is mini mobile filtration with a mixture of activated carbon and bidara leaf powder can reduce COx, SOx, and particulate matter values.